Los programas especiales del SINEM, su modelo pedagógico, las necesidades e intereses de sus estudiantes y el enfoque de derechos humanos: análisis y sugerencias / SINEM special programs: pedagogic model, students' needs and interests, and the human... - Arguedas Quesada, Consuelo (Actualidades Investigativas en Educación, 2014)
El siguiente documento es un artículo que analiza el modelo pedagógico que utilizan los Programas Especiales del Sistema Nacional de Educación Musical (SINEM), en relación con las necesidades e intereses de la población estudiantil y el Enfoque de Derechos Humanos. Para recabar los datos se aplica la observación no participante, la entrevista, el cuestionario, el dibujo, la revisión bibliográfica y los videos. Esta información se sistematiza mediante cuadros y se triangula para el análisis correspondiente; de esta manera se obtienen consideraciones y sugerencias al respecto. Además, con los resultados obtenidos se ofrece información al personal docente y administrativo del SINEM, a padres y madres de la población estudiantil y a aquellas personas que estén interesadas en este tema. This document emerges as a result of the bibliographic review performed by the author in order to achieve her Master degree in Human Rights of Children and Adolescents, for the Graduate Program in Social Work at the University of Costa Rica. It develops several postulates of the SINEM Special Programs pedagogic models, related to Human Rights approach and the needs and interests of the students, as part of the theoretical background covering in this program. The data was obtained through passive observation, interviews, questionnaires, drawings, bibliographic reviews and videos. The information was systematized in order to be analyzed and several conclusions and suggestions were obtained. Furthermore, this document is intended to provide information to SINEM’s docent and administrative staff, parents of children attending the institution and people interested in this area.